The historical monuments of France (1898) (14577615669) - Hunnewell | James... (Wikimedia Commons, 1898)
Notice visuelle issue de Wikimedia Commons pour la demo du fonds documentaire.
Droits : Licence No known copyright restrictions via Wikimedia Commons
Keywords: histoire; iconographie; gravure; photographie; wikimedia commons; Iconographie